2020
DOI: 10.3389/fonc.2020.00405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DPP4 Inhibitors in Survival of Patients With Prostate, Pancreas, and Breast Cancer

Abstract: Background: Dipeptidyl peptidase-4 (DPP4), a cell surface protein, exhibits a crucial role in tumor biology and regulation of the immune system. We aim to study the impact of DPP4 inhibitors (DPP4i) in patients with prostate cancer (PRC), pancreatic cancer (PC) and breast cancer (BC). Methods: Using the SEER and Medicare linked database, we identified patients with PRC or PC or BC with coexisting type II diabetes mellitus between 2007 and 2015. Patients were classified into four groups: (1) not on either DPP4i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
0
26
1
1
Order By: Relevance
“…The inhibition of DPP4 led to the suppression of breast cancer tumor growth ( 51 ) and displayed a positive trend in OS of colorectal cancer ( 52 ) and prostate cancer ( 53 ). Analysis of colorectal cancer and lung cancer patients showed a similar trend toward beneficial effects associated with DPP4 inhibition ( 54 ); however, further studies are required on the clinical impact of DPP4 inhibition on tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of DPP4 led to the suppression of breast cancer tumor growth ( 51 ) and displayed a positive trend in OS of colorectal cancer ( 52 ) and prostate cancer ( 53 ). Analysis of colorectal cancer and lung cancer patients showed a similar trend toward beneficial effects associated with DPP4 inhibition ( 54 ); however, further studies are required on the clinical impact of DPP4 inhibition on tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early cell lines and animal studies on prostate cancer showed that increased expression of DPP-4 may play an important role as a factor suppressing the long-period progression of the disease [ 91 ]. But, recent results of clinical trials showed the opposite [ 92 , 93 ]. Such contrary results may be due to the activity of DPP-4 on many substrates, which were not present, nor taken into consideration during cell line studies.…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Recent retrospective cohort analysis of 15,330 patients with PC and diabetes showed that use of DPP-4 inhibitors only ( n = 441) (HR 0.77; 95% CI: 0.64–0.93) and in combination with metformin ( n = 820) (HR 0.80; 95% CI: 0.68–0.94) had a significant overall survival (OS) benefit compared to the reference group (not on either DPP4 inhibitors or metformin). In addition, DPP-4 inhibitors show a trend to bring neutral or favorable results in subgroup analyses of PC patients irrespective of the stage (stage I not reliable; stage II HR 0.70, 95% CI: 0.54–0.9; stage III HR 0.96, 95% CI: 0.26–3.55; stage IV HR 0,81 95% CI: 0.53–1.26), treatments with chemotherapy (HR 0.84, 95% CI: 0.65–1.08 with chemotherapy and HR 0.71, 95% CI: 0.53–0.95) without chemotherapy), androgen-deprivation therapy (ADT) (HR 0.87, 95% CI: 0.69–1.15 with ADT and HR 0.67, 95% CI: 0.5–0.84 without ADT), prostatectomy (HR 0.27, 95% CI: 0.04–2.00 with prostatectomy and HR 0.78, 95% CI: 0.65–0.95 with no prostatectomy), or radiation (HR 0.84, 95% CI: 0.59–1.19 with radiation therapy and HR 0.73, 95% CI: 0.58–0.91 without radiation therapy), however because of low sample size some of this data was not statistically significant [ 93 ].…”
Section: Dpp-4 Inhibitorsmentioning
confidence: 99%
“…Shah et al recently established that DPP4 inhibitors offer a significant survival advantage in prostate cancer [5]. Malignant prostate tissue was found to contain higher levels of DPP4/CD26 compared to benign tissue.…”
Section: Introductionmentioning
confidence: 99%